(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Gout is a chronic metabolic disorder caused by the accumulation of uric acid in the body, primarily affecting the joints with the formation of uric acid crystals. It is a condition that can lead to joint inflammation, pain, and, in severe cases, result in gouty nephropathy, a kidney disorder. In this article, we will explore the prevalence of gouty nephropathy among patients with gout, diagnostic methods used, and the role of specific markers such as serum creatinine, systatin C, and renal Doppler ultrasound in diagnosis.